(untitled) (Experimental biology, 2015)
It was observed the influence of vegetable supplements on the antagonistic activity of the association KG. It was shown that the antagonistic activity of the association KG against fungi the most strongly increased supplements seeds of such cultures as chickpeas, oats and lentils. Antagonism against yeast of the genus Candida increased with the addition of mung bean and chickpea. The antibacterial activity increased with the addition of beans and wheat.